The composition of sacarine substrates for ethanol production and the fermentative capacity Saccharomyces cerevisiae Pedra-2 (Research, Society and Development, 2020)
The production of ethanol in Brazil is based on sugarcane juice, however other biomasses can be used for this process, such as sweet sorghum. However, some nutrients can interfere with fermentation, such as the presence of metals, carbon and nitrogen sources, which can affect the fermentation capacity of yeasts. Thus, this study aims to analyze the presence of fundamental nutrients present in saccharine substrates, as well as their assimilation and conversion of ethanol by the yeast Pedra-2. Samples of sugarcane and sorghum juice were obtained, in which analysis of the presence of metals was carried out using acid digestion and the levels determined by atomic flame absorption spectroscopy. The amino acid analysis was performed on the saccharine substrates at a concentration of 22 ºBrix, before and after fermentation, and analyzed by high-performance liquid chromatography and the concentration of ethanol by gas chromatography. The sorghum broth showed higher amounts of available amino acid metals. The yeast Pedra-2 showed better fermentative performance in the sorghum broth. We can conclude that the sorghum broth represents an important substrate to be used to increase the sustainability and production of ethanol in Brazil.